The Intervening Role of Work Environment Intervention: The Influence of Transformational Leadership and Career Development on Employee Engagement - Rahma Nadia Febrianti; Ryan Basith Fasih Khan (Pusat Penelitian dan Pengabdian Pada Masyarakat (P3M) STIE Pasundan, 2024)
This research investigates the impact of Transformational Leadership and Career Development on Employee Engagement, with Work Environment serving as a mediating variable. This study employs a quantitative research method, targeting employees of BBPPMPV BOE in Malang City. A sample of 144 participants was selected using Slovin's formula, maintaining an error level of 5%, and the sampling technique utilized was Simple Random Sampling. Data collection occurred through an online questionnaire, followed by data analysis using smartPLS. The findings reveal that Transformational Leadership and Career Development do not directly influence Employee Engagement. However, Employee Engagement significantly impacts the Work Environment, which in turn plays a crucial role in enhancing Transformational Leadership and Career Development. Furthermore, Employee Engagement lacks a direct effect on Transformational Leadership and Career Development; rather, its influence is mediated by the Work Environment. These results imply that while fostering a supportive Work Environment can strengthen the effects of Transformational Leadership and Career Development on Employee Engagement, organizations should focus on improving this environment to enhance overall employee involvement and satisfaction. This research underscores the importance of cultivating a positive workplace atmosphere to optimize leadership efficacy and career growth opportunities.